Catecholamine-dependent β-adrenergic signaling in a pluripotent stem cell model of Takotsubo cardiomyopathy - Borchert, Thomas; Haas, Jan; Meder, Benjamin (JACC Clinical electrophysiology, 2017)
Background: Takotsubo syndrome (TTS) is characterized by an acute left ventricular dysfunction and is associated with life-threating complications in the acute phase. The underlying disease mechanism in TTS is still unknown. A genetic basis has been suggested to be involved in the pathogenesis. Objectives: The aims of the study were to establish an in vitro induced pluripotent stem cell (iPSC) model of TTS, to test the hypothesis of altered β-adrenergic signaling in TTS iPSC-cardiomyocytes (CMs), and to explore whether genetic susceptibility underlies the pathophysiology of TTS. Methods: Somatic cells of patients with TTS and control subjects were reprogrammed to iPSCs and differentiated into CMs. Three-month-old CMs were subjected to catecholamine stimulation to simulate neurohumoral overstimulation. We investigated β-adrenergic signaling and TTS cardiomyocyte function.Results: Enhanced β-adrenergic signaling in TTS-iPSC-CMs under catecholamine-induced stress increased expression of the cardiac stress marker NR4A1; cyclic adenosine monophosphate levels; and cyclic adenosine monophosphate-dependent protein kinase A-mediated hyperphosphorylation of RYR2-S2808, PLN-S16, TNI-S23/24, and Cav1.2-S1928, and leads to a reduced calcium time to transient 50% decay. These cellular catecholamine-dependent responses were mainly mediated by β1-adrenoceptor signaling in TTS. Engineered heart muscles from TTS-iPSC-CMs showed an impaired force of contraction and a higher sensitivity to isoprenaline-stimulated inotropy compared with control subjects. In addition, altered electrical activity and increased lipid accumulation were detected in catecholamine-treated TTS-iPSC-CMs, and were confirmed by differentially expressed lipid transporters CD36 and CPT1C. Furthermore, we uncovered genetic variants in different key regulators of cardiac function.Conclusions: Enhanced β-adrenergic signaling and higher sensitivity to catecholamine-induced toxicity were identified as mechanisms associated with the TTS phenotype. (International Takotsubo Registry [InterTAK Registry] [InterTAK]; NCT01947621)
Gesehen am 12.04.2018